Fast Growing Plantations for Wood Production – Integration of Ecological Effects and Economic Perspectives - Bredemeier, Michael; Busch, Gerald; Hartmann, Linda; Jansen, Martin; Richter, Falk; Lamersdorf, Norbert P. (Frontiers in Bioengineering and Biotechnology, 2015)
Biomass crops are perceived as a feasible means to substitute sizeable amounts of fossil fuel in the future. A prospect of CO2 reduction (resp. CO2 neutrality) is credited to biomass fuels, and thus a potential contribution to mitigate climate change. Short rotation coppices (SRC) with fast growing poplar and willow trees are an option for producing high yields of woody biomass, which is suitable for both energetic and material use. One negative effect that comes along with the establishment of SRC may be a decrease in groundwater recharge, because high rates of transpiration and interception are anticipated. Therefore, it is important to measure, analyse, and model the effects of SRC-planting on landscape water budgets. To analyse the effects on the water budget a poplar SRC plot was studied by measuring hydrological parameters to be used in the hydrological model WaSim. Results reveal very low or even missing ground water recharge for SRC compared to agricultural land use or grassland, especially succeeding dry years. However, this strong effect on plot level is moderated on the larger spatial scale of catchment level, for which the modelling was also performed. In addition to water, nutrient fluxes and budgets were studied. Nitrogen is still a crucial issue in today's agriculture. Intensive fertilization or increased applications of manure from concentrated livestock breeding are often leading to high loads of nitrate leaching, or enhanced N2O emissions to the atmosphere on arable crop fields. SRC or agroforestry systems (AF) on former crop land may offer an option to decrease such N losses, while simultaneously producing woody biomass. This is mainly due to the generally smaller N requirements of woody vegetation, which usually entail no need for any fertilization. The trees supply deep and permanent rooting systems, which can be regarded as a "safety net" to prevent nutrient leaching. Thus, SRC altogether can help to diminish N eutrophication.